Factors influencing the acceptability of alcohol drinking for a patient with colorectal cancer. - Camille Auriol; Nicole Cantisano; Patrick Raynal (PLoS ONE, 2023)
Introduction Colorectal cancer is the second deadliest cancer worldwide. One of the risk factors for the development of this type of cancer is alcohol consumption. Patients with colorectal cancer may be stigmatized regarding their cancer and regarding drinking behaviors they may exhibit. This study aimed to analyze community persons' and health professionals' acceptability judgments regarding alcohol drinkers having colorectal cancer. Method This study relies on an experimental method enabling the identification of variables involved in one's judgment, based on the exhaustive combination of factors yielding several scenarios rated by participants. Scenarios implemented factors possibly influencing participants' perception of a woman character having colorectal cancer. Factors included her drinking habits, post-diagnosis drinking behavior and type of diagnosis/prognosis. The participants were community persons (N' = 132) or health professionals (N" = 126). Data were analyzed using a within-subject factorial ANOVA. Results In both samples, the "Post-diagnosis behavior" factor had large effect sizes, with drinking cessation being more acceptable than other drinking behaviors. Another factor, "Drinking habits", had significant influences on participants judgments, as higher drinking was considered less acceptable. A third factor, "Diagnosis" (polyps, early- or late-stage cancer), was taken into account by participants when it interacted with "Drinking habits" and "Post-diagnosis behavior". Indeed, participants considered most acceptable to continue drinking in the case of late-stage cancer, especially in the health professional sample where the acceptability of continuing drinking was almost doubled when the character had advanced- rather than early-cancer. Conclusion The lesser the drinking behavior, the better the acceptability. However, advanced cancer stage attenuated the poor acceptability of drinking in both samples, as participants' attitudes were more permissive when the patient had advanced cancer.